The Role of Green Products, Green Packaging, and Brand Loyalty in Influencing Green Purchase Decisions - Nataliya, Eblin; Nuvriasari, Audita (International Business Education Journal, 2023)
Green marketing practices have gained significant attention due to increasing consumer awareness regarding health-conscious and environmentally friendly products. This research aims to analyze the impact of green product, green packaging, and brand loyalty on the purchasing decisions of green milk “Frisian Flag”. Questionnaires were distributed to 100 consumers who consumed "Frisian Flag" green milk in Yogyakarta, Indonesia, and multiple regression analysis was conducted to test the research hypothesis. The analysis proves that green products do not have a significant effect on the decision to purchase green milk. However, green packaging and brand loyalty have significant positive influences on the decision to purchase "Frisian Flag" green milk. These findings indicate that environmentally friendly products are not a determining factor in the decision to purchase "Frisian Flag" green milk. The dominant factors influencing green milk purchase are green packaging and brand loyalty. Therefore, firms should allocate more investment for green packaging and developing brand loyalty to gain better competitive advantage.